Single-cell and spatial transcriptomics integration reveals FAM49B promotes tumor-associated macrophages polarization in colorectal cancer via the MK pathway - Liu, Tianyu; Ding, Quchen; Gou, Jin; Lu, Chen; Lu, Xingming; Chen, Jiatong; E., Yiming; Li, Lianhong; Zhang, Chongguo; Zhu, Xiaojuan; Yu, Chunzhao; Luo, Xiagang (Frontiers in Immunology, 2025)
ObjectivesFAM49B has been shown to promote proliferation and metastasis of colorectal cancer (CRC) by stabilizing MYC through phosphorylation of NEK9; however, its role in shaping the immune suppressive tumor microenvironment (TME), particularly in macrophage polarization, remains unclear.MethodsWe applied multi-omics approaches to study CRC by integrating 33 scRNA-seq samples from 16 CRC patients, 2 paired spatial transcriptomics (ST) samples, and bulk RNA data to characterize malignant epithelial cells (High_FAM49B_EP) and tumor-associated macrophages (TAMs). Functional validation of FAM49B was conducted via knockdown experiments and proteomics analysis.ResultsA High_FAM49B_EP subpopulation was identified in primary tumors (PT) and liver metastases (LM), exhibiting elevated MYC signaling and association with poor prognosis. TAMs showed spatial heterogeneity: M1-like CXCL3+ TAMs predominated in PT, whereas M2-like SPP1+ TAMs were enriched in LM. CellChat analysis revealed that High_FAM49B_EP activated macrophage polarization through the MDK–NCL signaling axis. Pseudotime trajectory analysis confirmed differentiation from CXCL3+ to SPP1+ TAMs driven by upregulation of NCL. Spatial mapping showed co-localization of MDK+ epithelial cells with NCL+ TAMs in the immunosuppressive microenvironment. FAM49B knockdown significantly inhibited MDK expression and disrupted ECM–receptor interactions.ConclusionsFAM49B promotes immunosuppressive TME formation by mediating TAM polarization via the MDK–NCL axis, suggesting the FAM49B–MDK–NCL pathway as a potential therapeutic target for CRC metastasis.